Wave-Induced Distribution of Microplastic in the Surf Zone - Kerpen, Nils B.; Schlurmann, Torsten; Schendel, Alexander; Gundlach, Jannek; Marquard, Daniel; Hüpgen, Markus (Frontiers in Marine Science, 2020)
In this study, the wave-induced distribution of 13 microplastic (MP) samples of different size, shape and density was investigated in a wave flume with a sandy mobile beach bed profile. The particle parameter were chosen based on an occurrence probability investigated from the field. MP abundances were analyzed in cross-shore and vertical direction of the test area after < 40,000 regular waves. It was found, that MP particles accumulated in more shallow waters with increasing size and density. Particles with high density (ρ>1.25g/cm^3 ) were partly stratified during the formation of the bed profile. Particles a density lower than the water floated constantly or deposited on the beach. A correlation was found between the settling velocity of the MP particles and the flow velocity at the accumulation point and a power function equation developed. The obtained results were critically discussed with findings from the field and further laboratory studies.